2021
DOI: 10.1111/ene.15192
|View full text |Cite
|
Sign up to set email alerts
|

Dural arteriovenous fistulas in cerebral venous thrombosis

Abstract: Background and purpose To explore the prevalence, risk factors, time correlation, characteristics and clinical outcome of dural arteriovenous fistulas (dAVFs) in a cerebral venous thrombosis (CVT) population. Methods We included patients from the International CVT Consortium registries. Diagnosis of dAVF was confirmed centrally. We assessed the prevalence and risk factors for dAVF among consecutive CVT patients and investigated its impact on clinical outcome using logistic regression analysis. We defined poor … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 34 publications
1
11
1
1
Order By: Relevance
“…A recent study found a 2.4% occurrence of dAVF in patients with CVST, with a higher incidence in those with chronic CVST onset, male gender, and increasing age. 3 This is in contrast to our young female patient.…”
Section: Sectioncontrasting
confidence: 96%
“…A recent study found a 2.4% occurrence of dAVF in patients with CVST, with a higher incidence in those with chronic CVST onset, male gender, and increasing age. 3 This is in contrast to our young female patient.…”
Section: Sectioncontrasting
confidence: 96%
“…A large retrospective series of 1218 individuals with CVT found a prevalence of new dural arteriovenous fistula of 2.4% at a median follow-up of 8 months (interquartile range, 5-23 months), although no systematic timing or neuroimaging protocol was included in the study. 29 A prospective study with systematic imaging collection at 6 months after CVT found no dural arteriovenous fistula. 30 The incidence of recurrent venous thromboembolism (VTE) after CVT ranges from 1% to 4% per year, with rates of CVT recurrence generally reported as <1% to 2% per year.…”
Section: Long-term Symptoms and Cvt Recurrencementioning
confidence: 98%
“…However, they may be encountered in children, 8 9 where they tend to be more extensive. 10 DAVFs are slightly more common in men, 11 12 but some studies have found that for certain types of DAVFs, such as those located in the cavernous sinus, incidence is equal or higher in women. 13 14…”
Section: Epidemiologymentioning
confidence: 99%
“…However, they may be encountered in children, 8,9 where they tend to be more extensive. 10 DAVFs are slightly more common in men, 11,12 but some studies have found that for certain types of DAVFs, such as those located in the cavernous sinus, incidence is equal or higher in women. 13,14 Pathophysiology DAVFs are believed to be secondary-acquired lesions that occur as a response to venous insults such as thrombosis, trauma, or infection.…”
mentioning
confidence: 99%